Extreme Weather and Civil War in Somalia: Does Drought Fuel Conflict through Livestock Price Shocks? - Jean-Francois Maystadt; Olivier Ecker; Athur Mabiso (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2013)
Climate change leads to more frequent and more intense droughts in Somalia. In a global context, weather shocks have been found to perpetuate poverty and fuel civil conflict. By relating regional and temporal variations in violent conflict outbreaks with drought incidence and severity, we show that this causality is valid also for Somalia at the local level. We find that livestock price shocks drive drought-induced conflicts through reducing the opportunity costs of conflict participation. Our estimation results indicate that a temperature rise of around 3.2 degrees Celsius?corresponding to the median Intergovernmental Panel on Climate Change scenario for eastern Africa by the end of the century?would lower cattle prices by about 4 percent and, in turn, increase the incidence of violent conflict by about 58 percent. Hence climate change will further aggravate Somalia's security challenges and calls for decisive action to strengthen both drought and conflict resilience, especially in pastoralist and agropastoralist livelihoods.
Keywords: 330; drought; conflict; civil war; livestock; prices; Somalia; Horn of Africa; Viehmarkt; Preis; Dürre; Bürgerkrieg; Somalia